Potensi Daun Genitri (Elaeoarpus Ganitrus) terhadap Profil Leukosit dan Histopatologi Lien Tikus Wistar Induksi Virus Influenza - Primiani, Cicilia Novi; Pujiati, Pujiati; Bhagawan, Weka Sidha (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Genitri (Elaeocarpus ganitrus) is a local plant, growing well in tropical forests. Genitri seeds are used as jewelry. Utilization of genitri in the health sector is still lacking. Objectif: To analyze the potential of genitri leaves on the leukocyte profile and splenic histopathology of Wistar rats. Methods: Experimental true approach, using experimental male wistar rats aged 5-6 months, weighing 280-360 grams, totaling 24 rats. Experimental animals were placed in group cages at 27oC, 12 hours of light, fed and watered ad libitum. Acclimatization was carried out 7 days before treatment. Treatment P0 (negative control), P1 induced influenza virus (Vaxigrip trivalent) 0.5 ml (positive control), P2 induced influenza virus 0.5 ml and 1 gram of genitri leaves. Induction of virus from intramuscular vaccine. Induction was carried out on day 0 and day 14. Genitri leaves were administered using the oral gavage method on the 3rd day for 29 days. On the 33rd day, blood sampling was carried out through the heart and surgery and spleen retrieval. Total leukocyte count using a hemocytometer. Histopathologically examined using hematoxylin and eosin (HE) staining. Results: The total leukocyte count on the 19th day, P0 4263.82 cells/mm3, P1 6314.46 cells/mm3, P2 8443.72 cells/mm3. Total leukocytes on day 33, P0 4241.66 cells/mm3, P1 4983.33 cells/mm3, P2 7520.83 cells/mm3. Diameter of germinal center spleen on day 19, P0 231 nm, P1 186 nm, P2 202 nm. Germinal center diameter on day 33, P0 239 nm, P1 191 nm, P2 242 nm. Tissue structure of the P1 spleen was congested and haemorrhagic, the structure of the spleen P2 had leukocyte infiltration, the marginal zone and germinal center were thickened. Conclusion: genitri leaves can increase the number of leukocytes and the diameter of the splenic germinal center of Wistar rats .